PENGARUH PENERAPAN PRINSIP-PRINSIP GOOD CORPORATE GOVERNANCE PADA KINERJA PEGAWAI - Andani, Vinda Ari; Riduwan, Akhmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to find out the influence of Good Corporate Governance principles which are represented by transparency, accountability, responsibility, autonomy, and fairness to the performance of the employees. The population is 30 employees of PT A.J. Central Asia Raya Surabaya. The data collection is carried out by using the primary data in the form of questionnaires. The multiple linear regressions analysis is applied as the data analysis method. The result of the research shows that (1) transparency has positive influence to the performance of the employees since this principle can improve the transparency of information about the company periodical, punctual and valid; (2) accountability has positive influence to the performance of the employees since accountability regulates how the company should form an audit committee to strengthen the internal control function by the commissioner; (3) responsibility has positive influence to the performance of the employees since responsibility principle regulates the fulfillment of companyâs responsibility as the business entity in the society to the entire stakeholders which include related issues in order to realize it as the finest company; (4) autonomy has positive influence to the performance of the employees since autonomy can regulate about how the employee can prevent the occurrence of unnatural domination of the stakeholders; (5) fairness has positive influence to the performance of the employees since it includes the clarity of shareholder rights in order to protect the interest of the shareholders including protection of minority shareholders from fraud.Keywords: Transparency, Accountability, Responsibility, Autonomy, and Fairness